The Impact of Macroeconomic Indicators and Bank Spesific Factors on Comercial Bank NPLs in the Province of South Sumatera - Oktaviani, Selvia; Yefriza, Yefriza (Universitas Batanghari Jambi, 2024)
Non-Perfoming Loan or non-performing loan is a ratio that can affect the stability of the banking financial system if NPLs are not managed properly, it will cause chaotic financial conditions and will cause economic problems.The purpose of this research is to examine the impact of macroeconomic indicators and bank-spesific factors on the Non Perfoming Loan ratio of commercial banks in Lampung Province. The study made use of time series data from 2010QI â€“ 2022QIV. The type of data used is secondary data obtain from the Central Bureua of Statistics and Bank Indonesia. The independent variabeles are macroeconomic indicators such inflation, exchange rate, BI rate, as well as bank-spesific factors such as LDR, with Non-Perfoming Loan serving as the dependent variable. This study employs multiple liniear analysis methods as well as traditional assumptions. The findings revealed that macroeconomic variables and bank specific indikators both affect NPL, with LDR having a partially negative effect on NPL. The exchage rate has a positive effect non-perfoming loans, while inflation and the BI rate have no effect.Â